PENGARUH LAYANAN BIMBINGAN KELOMPOK DENGAN TEKNIK JOHARI WINDOW TERHADAP PENINGKATAN KETERBUKAAN DIRI SISWA - Eli Zerni; Ferdi Ferdi; Nur Hamida Hasibuan; Titip Elyas; Wahidah Fitriani (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2026)
This study aims to analyze the influence of group guidance services with the Johari Window technique on increasing self-disclosure of class X students of MAS Darussalam Pinagar West Pasaman. The low self-openness of students can be seen from the lack of courage in expressing opinions, feelings, personal experiences, and difficulties in establishing effective social relationships. This study uses a quantitative approach with a pre-experimental method through a one-group pretest-posttest design. The study subjects amounted to 10 students who were selected using purposive sampling techniques based on low levels of self-openness. The research instrument is in the form of a self-disclosure questionnaire of 32 items that have been tested for validity and reliability. Treatment was provided through group guidance services with the Johari Window technique for five sessions. Data were analyzed using descriptive statistics and the Paired Sample t-test with the help of SPSS. The results of the study showed an increase in students' self-openness after participating in group guidance services with the Johari Window technique. The average self-openness score increased from 69.6 during the pretest to 104.5 during the posttest. Before treatment, 70% of students were in the low category and 30% in the very low category, while after treatment 50% of students were in the medium category and 50% in the high category. The results of the hypothesis test showed a significance value of 0.000 (< 0.05), which means that there is a significant influence of group guidance services with the Johari Window technique on increasing students' self-openness.